6-(2-x)6-x=3(4x-1)-4

Simple and best practice solution for 6-(2-x)6-x=3(4x-1)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(2-x)6-x=3(4x-1)-4 equation:


Simplifying
6 + -1(2 + -1x) * 6 + -1x = 3(4x + -1) + -4

Reorder the terms for easier multiplication:
6 + -1 * 6(2 + -1x) + -1x = 3(4x + -1) + -4

Multiply -1 * 6
6 + -6(2 + -1x) + -1x = 3(4x + -1) + -4
6 + (2 * -6 + -1x * -6) + -1x = 3(4x + -1) + -4
6 + (-12 + 6x) + -1x = 3(4x + -1) + -4

Combine like terms: 6 + -12 = -6
-6 + 6x + -1x = 3(4x + -1) + -4

Combine like terms: 6x + -1x = 5x
-6 + 5x = 3(4x + -1) + -4

Reorder the terms:
-6 + 5x = 3(-1 + 4x) + -4
-6 + 5x = (-1 * 3 + 4x * 3) + -4
-6 + 5x = (-3 + 12x) + -4

Reorder the terms:
-6 + 5x = -3 + -4 + 12x

Combine like terms: -3 + -4 = -7
-6 + 5x = -7 + 12x

Solving
-6 + 5x = -7 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-6 + 5x + -12x = -7 + 12x + -12x

Combine like terms: 5x + -12x = -7x
-6 + -7x = -7 + 12x + -12x

Combine like terms: 12x + -12x = 0
-6 + -7x = -7 + 0
-6 + -7x = -7

Add '6' to each side of the equation.
-6 + 6 + -7x = -7 + 6

Combine like terms: -6 + 6 = 0
0 + -7x = -7 + 6
-7x = -7 + 6

Combine like terms: -7 + 6 = -1
-7x = -1

Divide each side by '-7'.
x = 0.1428571429

Simplifying
x = 0.1428571429

See similar equations:

| 3k+6=4(k+2) | | 5x+3x=3x+2-3x | | 10-p=4p-7 | | x^2-10xy+16=0 | | |x/3|=3 | | 0=ln(x+2)-1 | | x-(v*v)=(w*w) | | (72x/8)(x^7/9x^3) | | a(-3)(-3)+7(-3)+b=0 | | 27=6(3+0.5m)-2m | | (1/435)*(2/3) | | 3.21(4.2y-5.1)=18.92 | | 1/435*2/3 | | X^2+12=-4 | | 7-4ln(x+5)=13 | | 7=11-3x | | 5x+3=8x-1.7 | | 5x+3.5=8x+1 | | 3a+2b+c=92 | | 3(x+103)=360 | | y=2.5+cosx | | -2+2ln(3x)=17 | | 3.2=0.32 | | -5x-2.9=-6-3.2 | | 3x+309=180 | | -1/3y-1/5 | | (5x-y+2)dx+(2x-y+1)dy=0 | | 3(x-4)=-2(x+3)+14 | | 6y-4y=8 | | x+2x+103=180 | | 2.4t-42.6=-9.2 | | 4x-17=7x-2 |

Equations solver categories